PENGEMBANGAN LKPD BERBASIS PEMBELAJARAN DI LUAR KELAS UNTUK MENINGKATKAN KEMAMPUAN INKUIRI DAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR - Agustin, Titin; Supeno; Prastiti, Tri Dyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The aim of this research is to describe the validity, practicability and effectiveness of LKPD based on learning outside the classroom. This type of research is R&D using the ADDIE model with stages, including analyze, design, development, implementation, evaluation. The research subjects were students in classes VIA, B, C at SDN Tanggul Wetan 02, Tanggul District, Jember Regency. Data collection techniques use observation, interviews, questionnaires, tests and documentation. The data analysis method used is preliminary data analysis, observation and interview data in preliminary research are analyzed using comparative analysis. Analysis of LKPD validity data, LKPD practicality data analysis, effectiveness data analysis. The results of the research showed that the validity of the syllabus, lesson plans, LKPD, teaching materials, learning outcomes tests was obtained in the mode value category 4 with an average reliability of above 89% and was declared valid/suitable for use. The practicality of LKPD development based on the assessment results of three observers in three classes stated that the LKPD developed was very practical and was at 89.62% to 90.69%. The effectiveness of developing LKPD based on out-of-class learning based on the N-Gain results obtained from the pre-test and post-test in classes A, B, and C was obtained in the high category, so it can be stated that LKPD based on out-of-class learning is declared effective and can be used. improve inquiry abilities and student learning outcomes.